2023
DOI: 10.3390/tropicalmed8020109
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccination Intention in Patients with Autoimmune Diseases in Indonesia: An Application of the Integrated Behavioural Model

Abstract: Vaccine hesitancy can be a challenge for those with autoimmune diseases. This study investigated the acceptance of COVID-19 vaccination by patients with autoimmune diseases in Indonesia using the integrated behavioral model (IBM). This cross-sectional study was conducted from December 2021 to February 2022. A total of 404 patients with autoimmune diseases completed the survey. The majority of respondents (57.9%) said they intended to get vaccinated against COVID-19. The IBM model with added demographic variabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…23 However, only 42.4% of autoimmune disease patients in Indonesia received COVID-19 vaccination. 24 In line with this, our study's immunization rate of only 49.0% was much lower than the Chinese overall population vaccination rate of 90.6%.…”
Section: Discussionsupporting
confidence: 76%
“…23 However, only 42.4% of autoimmune disease patients in Indonesia received COVID-19 vaccination. 24 In line with this, our study's immunization rate of only 49.0% was much lower than the Chinese overall population vaccination rate of 90.6%.…”
Section: Discussionsupporting
confidence: 76%
“…A qualitative study on understanding influenza pandemic based on rural community in Central Java found mixed opinions about Avian Flu as a rumor that have influenced their trust with the government's program to prevent Avian Flu cases [14]. To our knowledge, there have been limited evidence on risk perception, barriers and motivating factors that influencing the adoption of preventive measures towards COVID-19 in the context of Indonesia [15]. In order to fill this gap, a qualitative study was conducted to explore perception and factors underlying responses among adults in taking preventive measures towards COVID-19 in Indonesia.…”
Section: Introductionmentioning
confidence: 99%
“…However, during this study, little was known about the vaccine response in individuals with autoimmune rheumatic diseases and if they would mount an adequate immune response. Patients also expressed concerns about the vaccine’s potential impact on their immune system and whether it could trigger a flare-up of their condition [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%